Mixing enhancement with generation of effective secondary flow parallel to fluid interface in three-dimensional serpentine channel - Hyeonji Hong; Il Doh; Jaehwan Jeong; Eunseop Yeom (Results in Engineering)
Mixing efficiency is an important factor for various miniaturized systems that handle small volumes of samples. Serpentine channels, which are commonly employed for passive mixing, have been modified and designed based on three-dimensional (3D) structures. In this study, to investigate the effects of the sequential flow direction on mixing while considering the fluid interface, different models of 3D channels having the same length and number of bending parts were simulated under various Reynolds number conditions using liquid water as the working fluid. The mixing behaviors in these models varied because bends in different directions noticeably affected the mixing index. The mixing index increased when the net direction change of the secondary flow was varied, because of the relation of the mixing with the alignment between the fluid interface orientation and Dean vortices generated by the bending structure. Among the six designed models, the channel with the best mixing performance exhibited the most active interaction between the direction change of the secondary flow and fluid interface. Conversely, channels with a few direction changes exhibited low performances. To validate the simulation results, the mixing performances of two representative channels were experimentally compared using transparent 3D-printed chips. Similar to the simulation results, the 3D-printed chips showed noticeably different mixing performances.